Genotypic Analysis of Two Local Swamp Rice Based on Microsatellite Markers - Wage Ratna Rohaeni; Indrastuti A. Rumanti (Jurnal AgroBiogen, 2021)
Argo is a local swamp rice from Kalimantan which is widely cultivated by local farmers. Exploration activities in Kalimantan found two types of local rice named Argo but demonstrated different phenotypes. Therefore, genotypic verification is needed to determine the differences between the two Argo rice genotypes. DNA fingerprint could help genotype verification rapidly and the result is not influenced by environmental factors. The aims of this study were to determine the level of similarity of Argo-1 and Argo-2 with swamp rice and other irrigated rice genotypes using microsatellite markers. A total of eight improved and local varieties were used as genetic material with the two local rice Argo (Argo-1 and Argo-2). The rice genotypes were analyzed by using eight microsatellite markers. The results of the molecular analysis showed that the two types of Argo showed different DNA bands based on the RM228 marker but genetically they were closely related. The genetic distance between the two Argo cultivars is 0.143. Argo-1 and Argo-2 were located in the same cluster as Inpara 4 and Siam KDK, but they were in the different groups from those of irrigated rice varieties such as Mekongga and Inpari 9. Based on this research, Argo-1 and Argo-2 are not recommended to be crossed with Inpara 4 and Siam KDK because the genetic diversity formed will be narrow.